PELATIHAN MEMBATIK ECOPRINT GUNA MENUMBUHKAN JIWA KEWIRAUSAHAAN PEREMPUAN BAGI IBU-IBU RUMAH TANGGA - Alifiulahtin Utaminingsih (Publisher UPT P2M Politeknik Negeri Malang, 2020)
Entrepreneurship soul very important to growth to some one that have entrepreneurship spirit. That is some that do creatively and inovatively. Entrepreneur have characteristic improve skills, confidence have good self determination or locus of control, risk taker and look at change is chance for warehousing. There are farming ecologies so many leafs and flowers from any plants that can be use to make ecoprint batik models. Entrepreneurship trainning based on this condition so held trainning of batik ecoprint to increace skill for warehousing in Tegalweru village that economic creative based through ecoprint batik trainning to create new women entrepreneur in Tegalweri village, Sub District Dau, Malang Distric.